Tunicamycin Induces Hepatic Stellate Cell Apoptosis Through Calpain-2/Ca2 +-Dependent Endoplasmic Reticulum Stress Pathway - Liu, Haiying; Dai, Linyu; Wang, Ming; Feng, Fumin; Xiao, Yonghong (Frontiers in Cell and Developmental Biology, 2021)
It has been reported that calpain/caspase-mediated apoptosis induced by endoplasmic reticulum stress (ERS) in hepatic stellate cells (HSCs) by previous studies. At present, the activation of HSC is an important cause of liver fibrosis, and the induction of HSC apoptosis plays an irreplaceable role in reversing liver fibrosis. Therefore, it is of great significance to explore mechanisms of action that can induce HSC apoptosis for the reversal of hepatic fibrosis and the clinical prevention and treatment of hepatic-fibrosis-related diseases such as hepatitis, cirrhosis, and liver cancer. In the current study, we demonstrated that tunicamycin (a novel ERS inducer) can induce the apoptosis of HSCs and increase the concentration of intracellular Ca2+ and the expression of ERS protein GRP78, apoptosis protein caspase-12, and Bax, while it can decrease the antiapoptosis protein expression of Bcl-2. Our findings indicate that tunicamycin can induce HSCs apoptosis through calpain-2/Ca2+-dependent ERS pathway.